Lansia Sebagai Masyarakat Sadar Risiko Di Kampung Baru Kota Tanjungpinang - Novia Hardi Saputri; Sri Wahyuni; Emmy Solina (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
Being old is considered weak, unproductive, uncompetitive, a burden on the productive age and the state. When someone enters old age, there is a possibility that the elderly will be productive or unproductive. Generally, the elderly in the new village try to actualize themselves so that they are useful in living their old life by filling out activities dan carrying out their role as an elderly with the threats of the risks they face. The purpose of this study was to determine the activities of the elderly in the new village of Tanjungpinang city. The method used in this research is descriptive-qualitative method by examining phenomena that occur in society, namely the activities of the elderly at high risk dan their role in the family dan society with analysis using Ulrich Beck's theory of risk society. The results of this study indicate that the activities carried out by the elderly in the new village are divided into 2, namely activities inside the home dan outside the home. Family dan community views on the presence of the elderly in the new village. The elderly remain active in carrying out their roles dan activities, even though they are aware of the threatening risks. The forms of risk are physical risk, psychological risk dan social risk.